Enhanced adherence of Pasteurella multocida to porcine tracheal rings preinfected with Bordetella bronchiseptica. - Dugal, F (1992)
Adherence of 25 isolates of Pasteurella multocida to porcine tracheal rings was evaluated. Results indicated that adherence was not related to the isolate's origin, capsular or somatic types, dermonecrotoxin production or hemagglutination activity. The effect of a preinfection with Bordetella bronchiseptica on the colonization by P. multocida was then studied. On rings infected with P. multocida alone, bacteria initially adhered to the epithelium, but within a few hours, the level of colonization decreased progressively. On rings preinfected with B. bronchiseptica, or pretreated with a cell-free B. bronchiseptica culture supernate (or filtrate), a high level of P. multocida colonization was maintained for at least 24 hours. Results indicate that B. bronchiseptica appears to facilitate upper respiratory tract colonization by P. multocida by a process which involves a low molecular weight (less than or equal to 1000) heat-stable substance, possibly the tracheal cytotoxin.